Compact city development: High ideals and emerging practices - Hege Hofstad (Politecnico di Torino, 2012)
Compact city development has, over the last 20 years or so, emerged as the preferred response to the goal of sustainable development. As such, it is pertinent to examine planning practices to see whether the traditional economic bias in planning is now balanced by aims and practices in support of environmental and social sustainability. In this light the social, environmental, and economic goals linked to densification and mixed use development will be the main focus of this article. In addition, the article assesses whether distinct institutional practices support the balancing of these goals. The empirical basis is formed by urban plans in four Scandinavian cities in combination with qualitative interview data. The article concludes that on a discursive level, social, environmental and economic goals are represented in compact city strategies. Institutionalised practices, however, show that economic goals remain at the core of planning. Environmental and social aims still play second fiddle, but new measures are in development that may gradually strengthen their influence over urban development practices.